2022
DOI: 10.1007/s10508-021-02211-5
|View full text |Cite
|
Sign up to set email alerts
|

Diseases and Disparities: The Impact of COVID-19 Disruptions on Sexual and Reproductive Health Services Among the HIV Community in India

Abstract: People with HIV navigate numerous challenges to access healthcare in India. The lockdown in response to the COVID-19 pandemic presents further challenges in accessing sexual and reproductive health (SRH) services. This research explored the impact of the pandemic on SRH services, and the depth of disruptions faced by people living with HIV (PLHIV) in accessing treatment. Using purposive sampling with maximum variation technique, we recruited and conducted 150 telephonic in-depth interviews with PLHIV and HIV c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Despite of considerable heterogeneity of settings and services, 14 out of the 31 included studies (45%) reported decreased testing or reduced lab monitoring during the COVID-19 pandemic resulting in delay in diagnosis. 15 , 22 , 25 , 26 , 28 , 29 , 33 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…Despite of considerable heterogeneity of settings and services, 14 out of the 31 included studies (45%) reported decreased testing or reduced lab monitoring during the COVID-19 pandemic resulting in delay in diagnosis. 15 , 22 , 25 , 26 , 28 , 29 , 33 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…A despeito das políticas de prevenção e manejo do agravo implementadas ao longo das últimas décadas, a crise social e econômica pela qual o país passa desde 2014, acrescida ao advento da pandemia da COVID-19desde 2020, faz com que os serviços de saúde sofram uma sobrecarga e sérias instabilidades, obstaculizando o acesso e a continuidade do cuidado (15) . dificuldade no acesso e vinculação (16) , redução dos recursos humanos e materiais (17) , sobrecarga dos profissionais que atuam nos serviços assistenciais e de vigilância em saúde, entre outros (18) .…”
Section: Discussionunclassified
“…Therefore in-depth interviews using a semi-structured guide were used as the primary method of investigation in our study. The provider interviews were conducted as part of a larger study exploring the disruptions experienced by PLHIV while accessing sexual reproductive health rights and services during the COVID-19 pandemic and subsequent lockdown in India which occurred from March to May 2020 ( 12 ).…”
Section: Methodsmentioning
confidence: 99%